2021
DOI: 10.3390/ijms222011256
|View full text |Cite
|
Sign up to set email alerts
|

Polygodial and Ophiobolin A Analogues for Covalent Crosslinking of Anticancer Targets

Abstract: In a search of small molecules active against apoptosis-resistant cancer cells, including glioma, melanoma, and non-small cell lung cancer, we previously prepared α,β- and γ,δ-unsaturated ester analogues of polygodial and ophiobolin A, compounds capable of pyrrolylation of primary amines and demonstrating double-digit micromolar antiproliferative potencies in cancer cells. In the current work, we synthesized dimeric and trimeric variants of such compounds in an effort to discover compounds that could crosslink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…93,96 Monomeric ( 127 and 132 ) and dimeric ( 128 and 134 ) polygodial and ophiobolin A esters showed the same effects on human glioblastoma U373 cells, suggesting that their mode of action did not change with the dimerization. 99…”
Section: Ophiobolin Amentioning
confidence: 99%
“…93,96 Monomeric ( 127 and 132 ) and dimeric ( 128 and 134 ) polygodial and ophiobolin A esters showed the same effects on human glioblastoma U373 cells, suggesting that their mode of action did not change with the dimerization. 99…”
Section: Ophiobolin Amentioning
confidence: 99%
“…Recently, Maslivetc et al synthesized ethylene glycol-linked dimers of polygodial (2) (Figure 15) [69]. Antiproliferative effects of 74a and 74b were increased compared to polygodial (2).…”
Section: Semi-synthetic Drimane Derivativesmentioning
confidence: 99%
“…The increased cytotoxicity of 74a and 74b is explained by the ability to crosslink antitumor targets by pyrrole formation with lysine residues. However, no crosslink adducts were identified by Maslivetc et al [69]. Antiproliferative effects of 9-epipolygodial ( 49) and the Wittig derivative 64 were investigated more intensively [67,68].…”
Section: Semi-synthetic Drimane Derivativesmentioning
confidence: 99%
“…PG also exhibits antifungal, anti-inflammatory, and anticancer activity [ 29 , 30 , 31 ]. Several studies have reported that PG and its derivatives, including isopolygodial, 9-epipolygodial (DR-P27), 1-β-(p-coumaroyloxy)-polygodial, and 1-β-( p -methoxycinnamoyl)-polygodial, exhibit anticancer activity in different cancers [ 32 , 33 , 34 , 35 ]. Dasari et al [ 30 ] reported that DR-P27 possesses superior antiproliferative efficacy compared to PG in drug resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%